EP 16. Motor unit counting using automated threshold tracking techniques (MSCAN) in amyotrophic lateral sclerosis. Issue 9 (September 2016) - Hohmann, M.; Stubendorff, B.; Gunkel, A.; Ringer, T.; Prell, T.; Witte, O.W.; Grosskreutz, J.
Abstract : Introduction: Different motor unit number estimations methods were described in the last years to quantify the loss of motor units underlying ALS, a deadly neurodegenerative disease. MUNIX as a fast new technique relies on surface interference patterns (SIP) recorded during voluntary isometric contractions. In contrast, the recently developed MSCAN techniques is based on threshold tracking and uses natural threshold oscillations of single acons to identify the number of motor units present. MSCAN allows to estimate the composition of the CMAP from single units and contains a plethora of information on these units. Both studies require approximately 5 minutes per muscle and an optimal CMAP as starting point. Objective: Our goal was to implement MSCAN as a routine procedure in a specialized neuromuscular unit under realistic medical care conditions, to determine variability and benefit in clinical routine in ALS patients. Methods: MSCAN measurements were performed in 35 ALS patients in a cross-sectional in up to four muscles in the less affected side (APB, ADM, TA, EDB) in our neuromuscular unit by threshold-tracking experienced personnel. In addition, in a proband subset measurements using monopolar or bipolar stimulation were used. To minimize movement artifacts limbs were fixed using vaccum cushions. Disease duration, ALSFRS-R, Progression rate, ALSFRS-R subscores, diagnostic certainty and clinical stage were extracted from our local database which is an integral part of patient care and continuously reports patient status. Results: 5 Controls were 47.3 y (m 44.9, n  = 3 and f 50.8, n  = 2), Patients were 57.6y old (m 53.0, n = 20 and f 59.8, n = 15). Disease Duration was 26.4 mo (m 27.0, f 23.8), ALSFRS-R was 36.1 (m 36.5, f 33.2). Mean progression rate was 0.6 (both m and f 0.6). Bulbar subscore was 9.8 (m 10.7, f 7.9), cervical subscore was 8.5 (m 8.1, f 8.5), lumbar subscore was 7.4 (m 7.0 and f 7.3) and ventilation subscore 10.4 (m 10.7, f 9.4). MSCAN Units were significantly. Conclusion: MSCAN measurements in clinical routine are feasible, show a reduction of motor units in ALS patients compared to controls and correlate well with the CMAP. The correlation with functional measures was limited, likely due to the focal nature of the measurement. MSCAN values were more reduced in APB than in ADM, supporting the concept of a split hand syndrome often observed in ALS patients. Longitudinal studies are required to estimate the value of MSCAN as a prognostic and disease monitoring marker. Acknowledgment: This research is supported by BMBF (Bundesministerium für Bildung and Forschung) in the framework of the E-RARE programme (PYRAMID) of the European Union.